2012
DOI: 10.4028/www.scientific.net/amm.253-255.403
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Transition Zone Meso-Structure of MgO Concrete Loaded to Failure by Computed Tomography

Abstract: The computed tomography was introduced to track the development of cracks in cement matrix and interfacial transition zone of MgO concrete under load to failure. Results indicated that some pores were present before concrete was loaded due to none compaction which would tend to initiate cracks expanding. After loading, energy transferring route kept changing and extended towards weak area and it chose to be released through aggregates when concentrated stress on cracks tip surpassed ultimate load with conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…ere have been quite a few studies on the microstructure of cementitious composites containing reactive MgO, by means of X-ray diffraction (XRD) and thermogravimetric analyses [11,23,[31][32][33][34][35][36], specifically on the formation of Mg(OH) 2 and M-S-H phases [16,37]. Various reports based on SEM analyses have suggested that the hydration products of MgO exhibit a tendency to migrate towards the interfacial transition zone (ITZ) area thereby reducing the porosity of the resulting material [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…ere have been quite a few studies on the microstructure of cementitious composites containing reactive MgO, by means of X-ray diffraction (XRD) and thermogravimetric analyses [11,23,[31][32][33][34][35][36], specifically on the formation of Mg(OH) 2 and M-S-H phases [16,37]. Various reports based on SEM analyses have suggested that the hydration products of MgO exhibit a tendency to migrate towards the interfacial transition zone (ITZ) area thereby reducing the porosity of the resulting material [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%